Pengembangan Kantin Wirausaha Siswa SMPN 2 Porong - Masruchin Masruchin; Eni Fariyatul Fahyuni; Bayu Hari Prasojo (Jurnal Surya Masyarakat, 2020)
Entrepreneurship in this time is still less echoed because the ratio of entrepreneurs in Indonesia is meager. The community of conducted at Porong 2 state middle school various problems by empowering the existence of students' entrepreneurial canteens to have entrepreneurial skills, courage to face challenges, and entrepreneurial independence. This method of implementing into several stages, including 1) the planning stage, 2) the organizing stage, 3) the implementation stage, 4) the monitoring and evaluation stage, 5) the follow-up stage. The development and empowerment of entrepreneurship canteens in schools effectively makes students more active, productive and responsible in their lives